SETAN SETAN SEBAGAI MAF’UL BIH (OBJEK) DAN MAKNANYA DALAM AL-QUR’AN - St. Fauziah (Al-Ishlah: Jurnal Pendidikan Islam, 2023)
ABSTRACT This study discusses the position of Satan as maf'ul bih (object) in the Qur'an from the perspective of Islamic education. This study explores the meaning of Satan as maf'ul Bih (object) in sentences. In answering the problem, the writer uses a lexical semantic and grammatical meaning approach to see the values of Islamic Education in the Qur'an. This research is classified as library research, data is collected, then analyzed from representative literature and has relevance to the issues discussed, then reviewed, then concluded (verification). Here, data collection was carried out by exploring various literature, Arabic language books and research results, both from primary and secondary data. The results show that the word Satan as maf'ul bih (object) in the Al-Qur'an as a whole discusses the prohibition of following Satan's steps in all matters, both in attitude, character and actions; as well as reveal secrets about losses for the perpetrators (people who make Satan as a protector); the way to get rid of Satan's disturbances, namely by being grateful for Allah's Favors and in this research it is also revealed what the consequences if obedience to Allah will strengthen the heart, and strengthen the soles of the human feet, then the description of the groups that will be put into hell are people who follow Satan's words and whispers. And all of these verses contain the value of Islamic education: faith, worship, morals, and social.